REVIEW: GAMBARAN TINGKAT KESALAHAN PENGOBATAN PADA BEBERAPA RUMAH SAKIT DI INDONESIA - Adiningsih, Martha; Hermanto, Faizal (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
A medication error is any preventable event that can cause or result in inappropriate medication use or harm to the patient. Medication errors can occur in several phases or stages, namely prescribing errors, errors in translating prescriptions, errors in preparing and dispensing drugs, and errors in administering drugs. The aim of this article is to review and identify various levels of medication errors in several hospitals in Indonesia which are obtained from the percentage of medication errors. Based on a literature review conducted on 10 journals, article searches were carried out using two databases, namely Google Schollar and PubMed, the results obtained were that the most common medication errors occurring in several hospitals in Indonesia were the prescribing phase with a total distribution of levels of 7, then dispensing with a count of 2 and copying with a count of 1. Although medication errors remain a major challenge, with appropriate improvement efforts, patient safety in hospitals can be significantly improved)